What explains the German labor market miracle in the Great Recession? - Michael C. Burda; Jennifer Hunt (Institute for the Study of Labor (IZA), 2011)
Germany experienced an even deeper fall in GDP in the Great Recession than the United States, with little employment loss. Employers' reticence to hire in the preceding expansion, associated in part with a lack of confidence it would last, contributed to an employment shortfall equivalent to 40 percent of the missing employment decline in the recession. Another 20 percent may be explained by wage moderation. A third important element was the widespread adoption of working time accounts, which permit employers to avoid overtime pay if hours per worker average to standard hours over a window of time. We find that this provided disincentives for employers to lay off workers in the downturn. Although the overall cuts in hours per worker were consistent with the severity of the Great Recession, reduction of working time account balances substituted for traditional government-sponsored short-time work.
urn:nbn:de:101:1-20110629830
Keywords: E24; E32; J6; 330; unemployment; Germany; Great Recession; short time work; working time accounts; Hartz reforms; extensive vs. intensive employment margin